Tafsir Tematik-Sosial: Tawaran Pembacaan Hermeneutis M. Dawam Rahardjo dalam Menafsirkan Al-Qur’an - Akbar, Faris Maulana; Rahman, Yusuf (SUHUF, 2023)
This article attempts to examine M. Dawam Rahardjoʾs interpretation through his two works, Ensiklopedi al-Qurʾan: Tafsir Sosial Berdasarkan Konsep-konsep Kunci (The Encyclopedia of the Qurʾan: Social Interpretation Based on Key Concepts) and Paradigma al-Qurʾan: Metodologi Tafsir & Kritik Sosial (Paradigm of the Qurʾan: Methodology of Interpretation and Social Critique). In the treasures of Indonesian commentary literature, the two works of Rahardjo were unique, new and different at the time they appeared. The presentation in encyclopedic form and discussions that raise social issues make these work one of the pioneers of social-thematic interpretation. By using a descriptive-analytical method and a historical approach, this article attempts to trace and examine the ideas of interpretation in the two works hermeneutically to see how Rahardjo reads the Qurʾan in responding the social problems in society. The results of this study show at least three things: first, that Rahardjo’s interpretation from the beginning was directed to respond to ongoing social issues of his time; second, Rahardjo’s thinking was classified as progressive in his time because he attempts to solve social problems by integrating thematic interpretation with social science approach that he masters; third, his hermeneutical reading of the Qurʾan allows his interpretation to be relevant to the problems that exist in society.